2005
DOI: 10.1086/431442
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CEO Turnover on Equity Volatility*

Abstract: A change in executive leadership is a significant event in the life of a firm. Our paper investigates a potentially significant consequence of a CEO turnover: a change in equity volatility. We develop several hypotheses about how CEO changes might affect stock price volatility, and test these hypotheses using a sample of 872 CEO changes over the [1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995] period. We find that volatility increases following a CEO turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
166
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(186 citation statements)
references
References 42 publications
15
166
1
4
Order By: Relevance
“…Despite the advantages of analyzing specifically the sports industry, more research is necessary in order to see if comparable results can be obtained in other industries or on the basis of alternative firm performance metrics, respectively. Moreover, along the lines of Clayton, Hartzell & Rosenberg (2005), it would be instructive to investigate the impact of human resources turnover on stock price volatility. These will be the objectives of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of analyzing specifically the sports industry, more research is necessary in order to see if comparable results can be obtained in other industries or on the basis of alternative firm performance metrics, respectively. Moreover, along the lines of Clayton, Hartzell & Rosenberg (2005), it would be instructive to investigate the impact of human resources turnover on stock price volatility. These will be the objectives of future research.…”
Section: Discussionmentioning
confidence: 99%
“…This inquiry closely follows the approach of Dubofsky (1991) and Clayton et al (2005) in that the dependent variable is defined as the natural logarithm of the pre-event and event window volatility ratio. The application of the log transformation to the variance quotient reduces the skewness of the underlying data and thereby leads to more reliable t-statistics.…”
Section: Repeat Steps I and Ii 5000 Times And Sort The Collectmentioning
confidence: 99%
“…In conjunction, volatility in firms' stock prices following CEO transitions were also found to be higher for forced transitions than voluntarily or planned transitions (Denis and Denis, 1995). With regard to time period impact of executive transitions, another seminal study by Clayton et al (2005), employed a volatility event study methodology, which uses the log ratio of post-event to pre-event standard deviations. The authors found that volatility increases significantly in the first year following executive transitions of any type, with the highest volatility found in the first year following forced transitions (Clayton et al, 2005).…”
Section: Ceo Transitions and Impact On Returnsmentioning
confidence: 99%
“…With regard to time period impact of executive transitions, another seminal study by Clayton et al (2005), employed a volatility event study methodology, which uses the log ratio of post-event to pre-event standard deviations. The authors found that volatility increases significantly in the first year following executive transitions of any type, with the highest volatility found in the first year following forced transitions (Clayton et al, 2005). Given the importance of CEOs and CEO transitions for organizations, Lubatkin et al (1989) analysed the relevant horizon lengths that could be utilized to measure the impact of CEO transitions on organizations, and noted that although the typical two-day announcement period prevalent in the literature might be relevant, the impact of CEO transition on stock price could and should be measured across a variety of periods.…”
Section: Ceo Transitions and Impact On Returnsmentioning
confidence: 99%